Event Study: The Impact of Government Regulation Number 47 of 2024 on the Stock Market Reaction of Financial Sector Companies Listed on the IDX - Ningtyas, Fatmala Yulia Putri Utami; Azmiyanti, Rizdina (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2025)
The enactment of government regulation number 47 of 2024, which pertains to the elimination of non-performing loans for MSMEs, is constructive for MSMEs; however, investors have responded negatively. Utilizing a quantitative methodology, the investigation implements an event study. The research variables are abnormal return and trading volume activity, with a research observation period of 33 days. This period will include 16 days prior to the event, 16 days following the event, and 1 day during the policy enactment event. The purposive sampling technique was employed to select the sample from secondary data of 80 financial sector companies. Descriptive analysis tests, the Kolmogorov-Smirnov normality test, and the Paired Samples t-test hypothesis test comprise the research tests. The hypothesis test results suggest that the abnormal return variable does not exhibit any significant differences. Nevertheless, the trading volume activity variable exhibits a substantial disparity between the period prior to and following the policy enactment event. The findings of the research indicate that abnormal return are generally stable and decrease as trading volume activity increases. This suggests that investors are inclined to sell or release their shares when they are correlated, as evidenced by the abnormal return and declining stock price.